Exploring the Impact of Digital Literacy on Microtransaction Decisions in Online Gaming Among University Students - Rini Juliana Sipahutar; Suci Nurul Akhwatni Saragi; Khairunisah Ababil br Ginting; Enjelina Vincere Sihombing; Ines Manalu; Fitri Ananda Rambe; Ni Nyoman Salwa Khairunnisa (International Journal of Educational Practice and Policy, 2024)
This qualitative study explores the influence of digital literacy on microtransaction decision-making among university students engaged in online gaming. This demographic is significant as they exhibit varying levels of digital literacy and are key consumers in the gaming market. Through in-depth interviews with three purposively selected participants who have been active gamers for over five years, we analyze how digital literacy impacts behaviors related to virtual items. The findings indicate that students with higher digital literacy are better equipped to make informed purchasing decisions. In contrast, those with lower digital literacy struggle to discern reliable information, leading to impulsive buying behaviors and financial regret. The study highlights the important role of social influences and emotional engagement in spending decisions. Peer pressure and the desire for social acceptance often drive participants to make purchases that align with their friends’ behaviors, while emotional connections to games increase susceptibility to impulse buying. In conclusion, this research emphasizes the need to enhance digital literacy among gamers to empower informed financial decisions. By promoting digital skills, stakeholders can foster a healthier gaming environment that encourages responsible spending practices. Targeted educational initiatives are recommended to equip players with the tools necessary to navigate the complexities of microtransactions effectively, ultimately fostering more sustainable gaming habits.